Czech Republic : 2018 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2018)
This 2018 Article IV Consultation highlights that Czech Republic's growth has been strong, broad-based and job rich. The economy grew at 4.4 percent in 2017, led by strong domestic demand. The unemployment rate fell to a record low of 2.3 percent in April 2018, even with increased participation. Meanwhile, headline and core inflation are close to the target of 2 percent. Growth is projected to remain strong this year, at 3.7 percent, but labor shortages are putting constraints on future growth. In the near term, a decline in global trade is a major risk for a small economy highly dependent on external demand, particularly from the euro area, but also indirectly from other regions given how tightly integrated is the Czech economy into supply chains.